EPEN-21. SINGLE CELL RNASEQ IDENTIFIES A PUTATIVE CANCER STEM CELL POPULATION IN POSTERIOR FOSSA EPN. Issue 2 (22nd June 2018) - Donson, Andrew; Gillen, Austin; Riemondy, Kent; Hesselberth, Jay; Amani, Vladimir; Griesinger, Andrea; Witt, Davis; Hankinson, Todd; Handler, Michael; Vibhakar, Rajeev; Foreman, Nicholas
Abstract: Biological studies of ependymoma (EPN) have advanced our understanding of this tumor, but have relied heavily on bulk-tumor profiling. Intra-tumoral cellular heterogeneity within EPN bulk-tumor samples significantly confounds our understanding of the biology of this tumor, impeding development of effective therapy. We have addressed this problem using single cell RNAseq analysis (scRNAseq) of EPN, to characterize the cellular diversity within EPN tumor microenvironment. Using the 10x Chromium Drop-seq platform we analyzed approximately 3000 cells from 9 posterior fossa EPN patient samples. This approach identified 3 major cell subpopulations that were determined to be tumor based on shared EPN-specific gene expression. Two of these subpopulations exhibited molecular profiles indicative of (i) multiciliated border cells, and (ii) basement membrane cells, corresponding to the 2 major cellular populations present in normal ependymal cells from which EPN are thought to arise. The 3rd subpopulation harbored a cancer stem cell (CSC) gene signature, distinguished by upregulation of established stem-cell marker CD44 and stress-response genes, and low expression of ependymal differentiation genes. The abundance of this EPN subpopulations was estimated in primary tumor samples by deconvolution in a large cohort of clinically annotated EPN bulk-tumor transcriptomic profiles. A higher proportion of CSC or multiciliated cell populations was shown to determine assignment to transcriptomic subgroups PFA and PFB respectively. A higher proportion of CSCs was shown to be associated with a shorter survival than other EPN tumor subpopulations. Collectively, these findings support the hypothesis that this putative CSC subpopulation underlies tumor aggressiveness in posterior fossa EPN.